Coengagement enfant[s]-enseignant[e] dans le jeu partagé : penser le jeu comme un espace collaboratif et selon la perspective de ses acteurs - Marchand, Marie-Claude; Bouchard, Caroline; Robert-Mazaye, Christelle (Canadian Journal of Education/Revue canadienne de l'éducation, 2026)
Co-engagement between children and their teacher during shared play, all types of play combined, is complex to establish in the preschool classroom (Bouchard et al., 2021) but essential to implement, as it promotes children’s learning and development (Fleer, 2015). The aim of this thematic synthesis is to identify the elements perceived by children and teachers as influencing their co-engagement during jointed play. Following the Preferred Reporting Items for Systematic Reviews and Meta-analyses guide, 17 articles with qualitative or mixed methods were included. The data were thematized into 10 subcategories and classified into one of the three moments of sequential organization of joint play interaction, which included play signalling, play connection, and sustained co-participation (Pursi & Lipponen, 2018). The results show the importance of the presence of cognitive and affective reciprocity, enabling the play to be negotiated and perceived as a collaborative project in which each partner is important. This tipping point could be the foundation of a culture of play in the early children’s education field, leading favourably to children’s learning and development.